Decomposition, nitrogen release and weed control by prunings of selected alley cropping shrubs - Yamoah, C.F.; Agboola, A.A.; Mulongoy, K. (1986)
Decomposition of prunings and weed monitoring studies were conducted in a field under alley cropping with hedgerows ofCassia Siamea, Flemingia Congesta andGliricidia Sepium, at the International Institute of Tropical Agriculture, Ibadan, Nigeria. Decomposition of cutbacks and subsequent prunings ranged from 2.7 to 5.8% dry matter loss per week and the order was: gliricidia > flemingia > cassia for the cutbacks, and gliricidia > cassia > flemingia for the prunings. In 120 days, gliricidia cutbacks released 71% of the total N required by maize, flemingia, 26%, and cassia 77%. It appeared possible to supply the 29% N deficit in the gliricidia plots from a second pruning at about 66 days after planting (DAP) of maize. In the case of flemingia and cassia, external sources of N would be needed. During the fallow period, weed control was most effective under cassia, followed by gliricidia and flemingia, and during the cropping period, cassia mulch still maintained a fairly good weed control.